Zero Trust Security in WFA Platforms: A Literature Review of Principles, Challenges and Best Practices - Marafo, Melbert P.; Palay-en, Brein; Kiniway, Jofre Seth; Dulagan, Gilbert; Bugalin, Frederick; Bacasen, John; Guaki, Ginard S. (Southeast Asian Journal of Science and Technology, 2024)
The rise of Work-from-Anywhere (WFA) platforms has transformed work dynamics, offering flexibility while exposing organizations to heightened security risks that traditional perimeter-based security models cannot adequately address. This paper discusses crucial Zero Trust security principles applicable to WFA platforms, identifies best practices for implementation, and provides concrete recommendations for organizations that adopt these principles. A comprehensive literature review was conducted to examine existing research on Zero Trust frameworks and their application in WFA environments. Key principles such as least privilege access, continuous authentication, and network segmentation are emphasized as essential for safeguarding distributed workforces against unauthorized access and data breaches. Best practices for implementation include the use of Identity and Access Management (IAM) systems, continuous monitoring, and data encryption, all of which enhance security in WFA settings. The research highlights significant challenges such as integration with legacy systems, operational complexity, employee resistance, resource constraints, performance impacts, and scalability concerns. Addressing these obstacles requires phased implementation strategies, robust training programs, and adaptable solutions. This paper provides actionable recommendations, including prioritizing IAM, investing in monitoring technologies, enforcing network segmentation, and fostering a security-aware culture among employees. By adopting Zero Trust principles, organizations can effectively mitigate risks associated with remote work and enhance their overall security posture. Future research is encouraged to focus on industry-specific Zero Trust models and empirical evaluations to assess their long-term impact across diverse organizational contexts.